Respuesta :

Answer:

a=-2

b=4

c=-3

Step-by-step explanation:

You just compare -2x^2+4x-3=0 to

                              ax^2+bx+c=0

There is really no work here.

For this case we have that by definition, a quadratic equation is of the form:

[tex]ax ^ 2 + bx + c = 0[/tex]

The roots are given by:

[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}[/tex]

We have the following equation:

[tex]-2x ^ 2 + 4x-3 = 0[/tex]

So:

[tex]a = -2\\b = 4\\c = -3[/tex]

Answer:

[tex]a = -2\\b = 4\\c = -3[/tex]